Diagnostic Contribution of the DSM-5 Criteria for Internet Gaming Disorder - Luo, Tao; Wei, Dan; Guo, Jiangfan; Hu, Maorong; Chao, Xuelin; Sun, Yan; Sun, Qian; Xiao, Shuiyuan; Liao, Yanhui (Frontiers in Psychiatry, 2022)
Background: Internet gaming disorder (IGD) can have long-term severe consequences in affected individuals, especially adolescents and young people. Empirical studies of IGD using the DSM-5 criteria are still lacking. This study aimed to evaluate the contribution of specific criteria to the diagnosis of IGD based on the DSM-5 in the context of Chinese culture. Methods: The Chinese version of the Internet Gaming Disorder Scale–Short Form (IGDS9-SF) was applied to investigate the prevalence of IGD in a general sample of 28,689 middle school students aged 12-19 years from two cities in China. Results: The prevalence of IGD was 4.6% among this adolescent sample. The group of IGD students reported longer weekly gaming times and worse academic performance than the group of non-IGD students. Although ‘preoccupation’ and ‘playing to escape’ were the most frequently reported criteria, the conditional inference trees showed that ‘give up other activities’, ‘negative consequences’, and ‘continue despite problems’ contributed most to the diagnosis of IGD based on the DSM-5. Conclusions: The prevalence of IGD among Chinese adolescents (ages 12 to 19) was 4.6%. This study provides evidence for retaining or deleting specific diagnostic criteria by the DSM framework in the future.